Laser therapy as a therapeutic resource in speech therapy (Research, Society and Development, 2021)
The use of therapy using the Low Intensity laser is characterized by its multidisciplinary approach, since its use currently occurs by many professionals in different areas, such as speech therapists. Speech therapy professionals are already looking to use this therapy method, because it is non-invasive, that is, without toxic and collateral consequences, contributing significantly to therapies, by establishing a prognosis based on the excellence of the rehabilitation process.. The general objective of this research is to analyze what are the main contributions of laser therapy as a resource for the benefit of speech therapy. Among the specific objectives, the following stand out: to define laser therapy; identify the role of the speech therapist; to verify how laser therapy can be used by speech therapy professionals. The problem consists of the following question: how can laser therapy help speech therapy professionals in their skills? To support the research, there was a need for a methodology based on a bibliographic or literary review analyzing various sources, such as articles, monographs, dissertations, books and consultations on sites that provide scientific works, such as SCIELO and Google academic, for example. It is inferred that the research is pertinent, evidencing the various benefits of the use of laser therapy by speech therapy professionals, such as performance in facial paralysis, dysphagia, among others.